Coping with the cold: unveiling cryoprotectants, molecular signaling pathways, and strategies for cold stress resilience - Jahed, Khalil R.; Saini, Amolpreet Kaur; Sherif, Sherif M. (Frontiers in Plant Science, 2023)
Low temperature stress significantly threatens crop productivity and economic sustainability. Plants counter this by deploying advanced molecular mechanisms to perceive and respond to cold stress. Transmembrane proteins initiate these responses, triggering a series of events involving secondary messengers such as calcium ions (Ca 2+ ), reactive oxygen species (ROS), and inositol phosphates. Of these, calcium signaling is paramount, activating downstream phosphorylation cascades and the transcription of cold-responsive genes, including cold-regulated (COR) genes. This review focuses on how plants manage freeze-induced damage through dual strategies: cold tolerance and cold avoidance. Tolerance mechanisms involve acclimatization to decreasing temperatures, fostering gradual accumulation of cold resistance. In contrast, avoidance mechanisms rely on cryoprotectant molecules like potassium ions (K + ), proline, glycerol, and antifreeze proteins (AFPs). Cryoprotectants modulate intracellular solute concentration, lower the freezing point, inhibit ice formation, and preserve plasma membrane fluidity. Additionally, these molecules demonstrate antioxidant activity, scavenging ROS, preventing protein denaturation, and subsequently mitigating cellular damage. By forming extensive hydrogen bonds with water molecules, cryoprotectants also limit intercellular water movement, minimizing extracellular ice crystal formation, and cell dehydration. The deployment of cryoprotectants is a key adaptive strategy that bolsters plant resilience to cold stress and promotes survival in freezing environments. However, the specific physiological and molecular mechanisms underlying these protective effects remain insufficiently understood. Therefore, this review underscores the need for further research to elucidate these mechanisms and assess their potential impact on crop productivity and sustainability, contributing to the progressive discourse in plant biology and environmental science.